2020
DOI: 10.21203/rs.3.rs-51669/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Institutional Delivery Predisposes to Neonatal Sepsis and Its Associated Factors Among Neonates Admitted to Neonatal Intensive Care Units in Central Gondar Zone Primary Hospitals, Northwest Ethiopia, 2019.

Abstract: Background: Neonatal sepsis contributes substantially to neonatal morbidity and mortality and is an ongoing major global public health challenge particularly in developing countries. Studies conducted on proportion and risk factors of neonatal sepsis in Ethiopia are from referral hospital which may not be generalized to primary health care units where a significant proportion of mothers give birth in these health facilities. This study sought to determine the proportion of clinical neonatal sepsis and associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 18 publications
(36 reference statements)
2
7
0
Order By: Relevance
“…Neonates delivered at the home were 2.34 times more likely to develop sepsis compared to those delivered at the hospital [AOR = 2.34; 95% CI (1.4 to 4.8)]. This nding was similar to the study done in North West Ethiopia [4] and Nigeria [21] . This could be explained as neonates being born at home might lack skilled attendants, care for the umbilical cord, early breastfeeding, prophylaxis (application of tetracycline), and other infection prevention approaches and this may increase the risk of neonatal infection [9] .…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Neonates delivered at the home were 2.34 times more likely to develop sepsis compared to those delivered at the hospital [AOR = 2.34; 95% CI (1.4 to 4.8)]. This nding was similar to the study done in North West Ethiopia [4] and Nigeria [21] . This could be explained as neonates being born at home might lack skilled attendants, care for the umbilical cord, early breastfeeding, prophylaxis (application of tetracycline), and other infection prevention approaches and this may increase the risk of neonatal infection [9] .…”
Section: Discussionsupporting
confidence: 81%
“…Increased odds of neonatal sepsis were noted among mothers who have a history of more than 4 PV examinations during labor compared to mothers who had PV examinations less than or equal to 4 [AOR = 2.6; 95% CI [ (1.3 to 5.3]]. This nding was linked to a study done in Bangladesh [18] and North West Ethiopia [4] . This might be explained as multiple per-vaginal examinations can introduce vaginal organisms into the cervical canal, which, in turn, increases the risk of infection [19] .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…15,16 However, the prevalence of neonatal sepsis was lower in this study than in previous studies, which found a prevalence of 64.8% in Gondar primary hospitals in northwest Ethiopia, 77.9% in Shashemene hospitals in central Ethiopia, and 69.35% in Dhaka public hospitals in Bangladesh. [17][18][19] The difference could be attributed to the method by which neonatal sepsis is diagnosed. Clinical parameters alone were used to classify neonatal sepsis in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar manner in Ethiopia, neonatal sepsis continued an important public threat across all regions whereof different time Hospital-based studies showed different prevalence for overall, early and late onsets of neonatal sepsis. Accordingly, the overall prevalence of neonatal sepsis was 63.69% (EOS comprised 59.33%) in 2017 [26] and 64.8% in 2019 [27] at the University of Gonder, 78.3% at Arba Minch General Hospital in 2018 [28], 33.8% in Wolayita Sodo in 2018 [29], and 77.9% in Shashamane 10 Shigella…”
Section: Bacteriamentioning
confidence: 99%